Outcomes following radical prostatectomy or external beam radiation for veterans with Gleason 9 and 10 prostate cancer. (15th March 2022) - Chao, Hann‐Hsiang; Soni, Payal D.; Dahman, Bassam; Stilianoudakis, Spiro C.; Ford, Hampton; Singh, Raj; Freedland, Stephen J.; Moghanaki, Drew; Vapiwala, Neha; Chang, Michael G.
Abstract: Background: The optimal upfront treatment modality for patients with nonmetastatic Gleason Score 9 and 10 prostate cancer (GS 9–10 PCa) is unknown. Methods: We conducted a retrospective cohort study of patients in the Veterans Health Administration (VHA) with GS 9–10 PCa treated with radical prostatectomy (RP) or external beam radiation therapy with androgen deprivation therapy (EBRT+ADT) from 1/2000 to 12/2010. Outcomes included overall survival (OS), distant metastasis‐free survival (DMFS), and salvage/adjuvant therapy‐free survival (SAFS), as assessed by Kaplan–Meier analysis. Results: We identified 1220 veterans with GS 9–10 PCa; 335 were treated with RP, and 885 were treated with EBRT+ADT. With a median follow‐up of 9.9 years, propensity score‐matched analyses demonstrated that RP had superior 10‐year OS (70.8% [RP] vs. 61.2% [EBRT+ADT], p  < 0.001), 10‐year DMFS rates were similar between RP (76.7%) and EBRT+ADT (81.0%), and 10‐year SAFS rates were lower for RP vs EBRT + ADT (35.2% [RP] vs. 75.2% [EBRT+ADT], p  < 0.001). The receipt of salvage ADT was higher with upfront RP (51.9% vs. 26.1%, p  < 0.001), despite receipt of adjuvant/salvage EBRT in 41.8% of RP patients. Among patients treated with RP, there were no differences in outcomes by race. However, higher survival rates were noted among Black patients treated with EBRT+ADT compared with White patients. Conclusions: This analysis demonstrated higher 10‐year OS rates among men treated with upfront RP versus EBRT+ADT, though missing confounders and similar DMFS rates suggest the long‐term cause‐specific OS rates may be similar. We also highlight real‐world outcomes of a diverse patient population in the VHA and improved outcomes for Black patients receiving EBRT+ADT. Abstract : In our Veteran cohort of 1220 patients diagnosed 2000‐2010 with Gleason 9‐10 prostate cancer, patients had similar distant‐metastases free survival with either upfront RP or EBRT+ADT. Black versus White men had similar outcomes with RP and superior outcomes with EBRT+ADT. Men with Gleason score 9‐10 PC can achieve similar long‐term oncologic outcomes with either upfront RP or EBRT+ADT, but the burden and toxicities of treatment can differ depending on the treatment choice.